Photocatalytic Removal Of 2, 4- Dichlorophenoxyacetic Acid And Quinclorac Herbicides By An Immobilized System Of Carbon Coated, Nitrogen Doped And Polyene Sensitized TiO2 - Ahmad Sabri, Nur Nazrina (2017)
An immobilized system of carbon coated, nitrogen doped and polyene sensitized TiO2 (CNTiO2/EP-10h) was fabricated using epoxidized natural rubber (ENR50) and polyvinyl chloride (PVC) as the binders through a dip coating technique. The optimum amount of photocatalyst and PVC binder in the coating formulation were 6 g and 0.8 g, respectively, while 2.29 mg cm-2 was the best amount of photocatalyst composite loading. The photo-etching process for 10 hours (10h) reduced the band gap energy of the photocatalyst from 2.91 to 2.86 eV, creating a highly porous photocatalyst surface as well as oxidizing the PVC binder to be a conjugated polyene that sensitized TiO2.